2019
DOI: 10.1111/acps.13089
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and computational modelling analysis of unilateral montages in electroconvulsive therapy

Abstract: S, Loo CK. A systematic review and computational modelling analysis of unilateral montages in electroconvulsive therapy Objective: To examine the clinical outcomes of ECT unilateral placements compared in prior studies and apply insights from computational modelling to understand differences between placements. Methods: PubMed, Embase, Scopus and PsycINFO and reference lists were systematically searched for studies of depressed patients where two unilateral placements were compared and clinical outcomes were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…D. Martin et al demonstrated some evidence to reach the best cognitive profile in favor of frontalfrontal and frontal-parietal placement relative to the temporoparietal position. Furthermore, this study showed better verbal anterograde memory outcome in the right unilateral placement in comparison to the left unilateral placement (20).…”
Section: Recommended Approach In Case Of Severe Cognitive Impairment ...mentioning
confidence: 48%
See 1 more Smart Citation
“…D. Martin et al demonstrated some evidence to reach the best cognitive profile in favor of frontalfrontal and frontal-parietal placement relative to the temporoparietal position. Furthermore, this study showed better verbal anterograde memory outcome in the right unilateral placement in comparison to the left unilateral placement (20).…”
Section: Recommended Approach In Case Of Severe Cognitive Impairment ...mentioning
confidence: 48%
“…Most of the literature suggests that cognitive state is usually affected by ECT (18)(19)(20). The results of this study showed that more than 80% of the experts believe that the cognitive assessment is necessary before and after ECT; nonetheless, only 15% of the specialists referred patients for cognitive evaluation.…”
Section: Discussionmentioning
confidence: 79%
“…Acute retrograde amnesia for information acquired immediately prior to the administration of a single ECT treatment is also common. These side effects have been observed across multiple different memory domains, are typically large in magnitude (Martin et al, 2019) and are sensitive to ECT treatment factors, including electrode montage (Prudic et al, 1994), dose (Sackeim et al, 1993) and pulse width (Loo et al, 2015;Sackeim et al, 2008). While acute cognitive side effects other than memory have also been investigated (e.g.…”
Section: Acute Cognitive Side Effectsmentioning
confidence: 99%